Splendour of power the Wettins on the throne of the Polish-Lithuanian Commonwealth - Łagocka, Maja; Zychowicz, Izabela (Royal Łazienki Museum in Warsaw, 2022)
The exhibition, which took place at the Royal Łazienki from November 2021 to February 2022, was the first attempt since 1997 to promote knowledge of the common Polish-Saxon history, the legacy which, in the present times, can still be seen both in Dresden and in Warsaw. The exhibition depicts Augustus II and Augustus III as conscious art collectors and connoisseurs who, in a period of 66 years of the Polish-Saxon Union, amassed one of the most important and magnificent art collections in 18th century Europe. The exhibition presented the most outstanding examples of the Wettin House’s cultural policy. These are 200 works from Dresden and Polish collections, i.e. Staatliche Kunstsammlungen Dresden, Sächsische Hauptstaatsarchiv Dresden, The Museum of the Royal Castle in Warsaw, the National Museum in Warsaw, the Print Room of the Warsaw University Library, the Wawel Royal Castle, the Pauline Monastery in Jasna Góra and the Museum-Castle in Kórnik
Frontispizseite: Exhibition: Royal Łazienki Museum in Warsaw, Officer Cadet School, Palace on the Isle, 5 November 2021 - 27 February 2022
Keywords: Wettiner -- Familie; Geschichte 1700-1800; Höfische Kunst; Wettynowie / (dynastia); Muzeum Łazienki Królewskie (Warszawa); Ceramika artystyczna; Grafika europejska; Malarstwo europejskie; Rzemiosło artystyczne; Rzeźba europejska; Sztuka europejska; Wystawy sztuki; Warszawa (woj. mazowieckie); 1601-1700; 1701-1800; 1801-1900; Katalog wystawy; Publikacja bogato ilustrowana; Ausstellungskatalog -- Muzeum Łazienki Królewskie -- 05.11.2021-27.02.2022 -- Warschau